PERLINDUNGAN HUKUM BAGI TENAGA KERJA PENYANDANG DISABILITAS UNTUK MENDAPAT KESEMPATAN KERJA BERDASARKAN UNDANG UNDANG NOMOR 08 TAHUN 2016 TENTANG PENYANDANG DISABILITAS - Sari, Rahma (Journal of Law ( Jurnal Ilmu Hukum ), 2022)
AbstractThis study discusses the workforce is part of the subject of employment which is considered capable of doing a job in order to produce goods or services both to meet the needs of themselves and the community. Protection for Workers, especially Workers with disabilities where the government guarantees the safety and existence of workers with disabilities is recognized by the community in general. Explicitly in international legal provisions that position persons with disabilities as part of citizens whose rights must be fulfilled in the perspective of Human Rights, contained in Law Number 8 of 2016 concerning Persons with Disabilities, the regulation refers to previous regulations issued by the government, namely Law Number 19 of 2011 concerning Ratification of the Convention on the Rights of Persons with Disabilities, and Law Number 4 of 1997 concerning People with disabilities. Through research, this thesis seeks to answer existing problems using normative juridical methods, so from the research that has been carried out a conclusion can be drawn, that the government legislation has provided legal protection for workers with disabilities in obtaining job opportunities according to the Act. The 1945 Constitution of the Republic of Indonesia and the laws and regulations that are enacted with reference to the theory of human rights. The form of fulfillment of workers with disabilities in obtaining employment opportunities is through affirmative policies that must be implemented by inserting them into regulations that have been issued by the government. Reforms that must be implemented in affirmative action policies in the field of accessibility in obtaining employment opportunities for workers with disabilities are the responsibility of the state towards workers with disabilities in fulfilling their rights.